Obstetric fistula among women aged 15-49 years in Zambia - Singini, Mwiza Gideon (My University, 2017)
Background An estimated 2,000 women in Zambia suffer from obstetric fistula. Suggestions are that more women could be suffering from the same condition but do not report it due to fear of stigmatization. Incidences of obstetric fistula in Zambia may indicate that most pregnant women do not access the much-needed maternal health services, especially at the time of delivery. Therefore, understanding the factors that lead to obstetric fistula is vital for developing primary preventive interventions. This study estimated the prevalence and investigated the factors associated with obstetric fistula among women in Zambia. Methodology The study used data from the 2013-14 Zambia Demographic and Healthy Survey (ZDHS). A sample of 16,411 women aged 15-49 years old took part in the fistula module of the ZDHS. Descriptive and Complementary log-log regression model were conducted to assess the relationship between the covariates and obstetric fistula. Results The prevalence of obstetric fistula was estimated at 5.91 obstetric fistulas per 1000 women of reproductive ages. Age at first sex (AOR=0.86, CI: 0.77-0.97) and being in households of rich wealth status (AOR=0.36, CI: 0.14-0.79) were negatively associated with obstetric fistula. Conclusion Evidence suggest that in order to eradicate obstetric fistula in Zambia, there is need to implement interventions that will focus on improving the socioeconomic, health status, reproductive status, access to health care and use of healthcare resources of women.
A research report submitted to the faculty of the Humanities at the University of Witwatersrand in partial fulfilment of the degree of Master of Arts in Demography and Population Studies, June 2017
Keywords: Obstetrics--Zambia; Women--Health and hygiene--Zambia; Reproductive health--Zambia